Productivity Enhancement by Implementing Automatic Burr Cleaning Machine in Lathes - R, Vishnu.; R, Raagav.; R, Karthik; A, Thamaraiselvan.; S, Palani. (International Journal of Engineering and Technology, 2018)
In the era of modernization and complete automation, industries employ manual cleaning operation which is highly time-consuming and man power requirements are high. To overcome this situation an automatic cleaning machine which can be employed to overcome the above stated obstacles by means of a completely automated cleaning system universally for different categories of machines based on the duties and classes of performance respectively.The main objective of this project is to develop a universal cleaning system which is used to completely clean the wastes which falls in between the machinery and at its collection spots such as hoppers, beds, plates, floors etc., where it cleans in all places where human hands cannot reach and cleaning operation considered not possible. The major advantage of machines are that they much more precise in doing the work than considered to a human or manual laborÂ Â